THE EFFECT OF DECELLULARIZATION TECHNIQUE ON COLLAGEN TYPE II AND MATRICES POROSITY OF CARTILAGE BOVINE SCAFFOLD - Dwikora Novembri Utomo; Ika Benny Kartika Sari (Journal Orthopaedi and Traumatology Surabaya)
Background: Cartilage has limited capacity for self-repair in case of defect. Stem cell based tissue engineering has become an alternative therapy for the treatment of cartilage defect. The use of decellularized cartilage bovine can serve as scaffold to support proliferation dan differentiation of the stem cell.